2002
DOI: 10.1088/0953-8984/14/17/320
|View full text |Cite
|
Sign up to set email alerts
|

Dimer interactions of magic W@Si12 clusters

Abstract: Design of stable Si-cage and Si-tube structures is of great importance to the fields of Si nanotechnology and microelectronics. In order to explore the possibility of constructing a Si nanotube by using the metal-stabilized and tube-shaped Si cluster W@Si12 as the basic unit, detailed first-principles calculations are performed to analyse the interactions of the dimers. It is found that the interactions are orientation dependent, and no interactions exist if stacking is along the sixfold axis. However, the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
(19 reference statements)
1
18
0
Order By: Relevance
“…In this way one-dimensional Si nanostructures can be fabricated, which is totally different from the situations in free space. 18 This can be understood as follows: The larger number of core electrons in Si makes it much more difficult for two Si atoms to form double or triple bonds. Conse- quently, Si prefers to form multidirectional single bonds (sp 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way one-dimensional Si nanostructures can be fabricated, which is totally different from the situations in free space. 18 This can be understood as follows: The larger number of core electrons in Si makes it much more difficult for two Si atoms to form double or triple bonds. Conse- quently, Si prefers to form multidirectional single bonds (sp 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is natural to imagine the possibility of constructing a one-dimensional chain of these caged clusters. However, detailed studies 18 of their dimer indicate that in free space the two clusters interact and consequently their structures are seriously destroyed. Thus it is difficult to construct a one-dimensional Si nanostructure in free space using this WSi 12 tube-shaped unit.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Silicon nanostructures such as Si 10 , Si 20 , M@Si n (M = Ti, W, Cr, Mo, Ba, n = 8-20) have been extensively studied both theoretically and experimentally, but one of the challenges for their application is how to assemble these structural units to make functional materials [8][9][10]. Here we show that Si-doped heterofullerene may provide a novel pathway for assembling carbon-silicon Janus nanostructures.…”
Section: Introductionmentioning
confidence: 91%
“…However, it has been found recently that C 60 cannot be used to stabilize Si 60 , while the magic clusters with 40 electrons such as Al 12 X (X ¼ Si, Ge, Sn, Pb) will do [17], because the magic cluster can be used as a superatom [18]. As for the one-dimensional Si structure, we found that the tube-like Si 12 W cluster cannot be used as the building block for the construction of 1D Si nano-structure [19], while encapsulating Si clusters into carbon nano-tube can fabricate onedimensional Si structure, and change effectively the electronic and optical properties of the system [20]. Therefore, the structure of Si can be tuned at nano-scale, and this new freedom provides flexible ways to design novel structures with exotic properties for the applications in physics, chemistry, materials science, and in microelectronics.…”
Section: Discussionmentioning
confidence: 79%